2016
DOI: 10.1080/14767058.2016.1253060
|View full text |Cite
|
Sign up to set email alerts
|

Impacts on prenatal development of the human cerebellum: a systematic review

Abstract: Current literature on associations between parental environmental exposures, intrinsic factors and human cerebellar development is scarce. Yet, this systematic review provided an essential overview of human studies demonstrating the vulnerability of the cerebellum to the intra-uterine environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 69 publications
(99 reference statements)
1
33
0
2
Order By: Relevance
“…The existing literature has identified some potential risk factors, mainly through animal studies and case reports, that we did not find among NBDPS cerebellar hypoplasia cases. Several studies, reviews, and case reports have found associations between prenatal infections, particularly viral infections, and cerebellar hypoplasia (Ceballos et al, ; de Fatima Vasco Aragao et al, ; Hazin et al, ; Koning et al, ; Melo et al, ; Meneses et al, ; Patel & Barkovich, ; Poretti, Wolf, & Boltshauser, ; Steinlin et al, ). Yet, the possible role of an infectious etiology remains unclear from our NBDPS results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The existing literature has identified some potential risk factors, mainly through animal studies and case reports, that we did not find among NBDPS cerebellar hypoplasia cases. Several studies, reviews, and case reports have found associations between prenatal infections, particularly viral infections, and cerebellar hypoplasia (Ceballos et al, ; de Fatima Vasco Aragao et al, ; Hazin et al, ; Koning et al, ; Melo et al, ; Meneses et al, ; Patel & Barkovich, ; Poretti, Wolf, & Boltshauser, ; Steinlin et al, ). Yet, the possible role of an infectious etiology remains unclear from our NBDPS results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis of prospective studies (including 1,255 carbamazepine exposure pregnancies) found an increased rate of neural tube defects, cardiovascular birth defects, urinary tract anomalies and cleft palate, in addition to a pattern of minor congenital anomalies and developmental delays (Matalon, Schechtman, Goldzweig, & Ornoy, 2002). We also explored maternal behavioral risk factors, including cocaine use, alcohol use, and smoking, all of which have been associated with cerebellar hypoplasia previously (Bellini et al, 2000;Ekblad et al, 2010;Koning et al, 2016;Norman et al, 2009). No mother of a cerebellar hypoplasia case in the NBDPS reported cocaine use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, based on the CBG knock‐out mice models, CBG and cortisol have been reported to be associated with neurocognitive functions (Meyer et al, ). Children exposed to an imbalance of cortisol in‐utero have cerebellar developmental problems (Koning et al, ). Of relevance are several adverse effects of exposure to long‐chain phthalates, such as DEHP in children (reviewed in [Braun et al, ]).…”
Section: Discussionmentioning
confidence: 99%